THE IMPORTANCE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING ENGLISH - Siddikova Sogdiana Mahammat Soli kizi, (TADQIQOTLAR, 2026)
Abstract: This article analyzes the role and importance of modern pedagogical technologies  in  the  process  of  teaching  English.  In  particular,  the  effectiveness  of interactive methods, information and communication technologies, multimedia tools and innovative approaches in the quality of education and the development of students' language  skills  is  highlighted.  During  the  study,  it  was  determined  that  modern technologies  serve  to  increase  students'  independent  thinking,  communicative competence  and  motivation.  The  advantages  of  using  digital  platforms  in  teaching English are also shown.